Perancangan Sistem Informasi Akuntansi Pendapatan Pada Arkan Graha Berbasis Web Menggunakan Php Dan Mysql - Kiki Hakiki Haryadi; Hery Dwi Yulianto (Labkat Press KA FTIK UNIKOM, 2017)
Arkan Graha are addressed in jl. Cisaranten kulon III No.14A Arcamanik Bandung 40293 (022 87882775). Arkan Graha requires a good income information systems to handle various problems in the company, which include the income or expenditure reporting services that still use ms.excel and performed by one person, doing so in the company's earnings report to be less effective. To these problems, the writer took the title